Factors Affecting Clinical Course and Mortality among COVID-19 Patients Receiving Convalescent Plasma Treatment - Sonmez, Ufuk; Atalay, Sabri; Abakay, Hilal; Çağlayan, Derya; Arı, Alpay; Özkarakaş, Hüseyin; Uğur, Esra (Tropical Health and Medical Research, 2022)
In this study, our research objectives are; to evaluate death risk covariates and the clinical course of the COVID-19 patients who had received convalescent plasma treatment. This study was performed between April 2020 -April 2021, retrospectively. The study was conducted at two centers in Izmir, Turkey. Demographic characteristics, number of plasma given, the time between the onset of the symptoms and the first plasma treatment, and laboratory results(C-reactive protein, white blood cell, thrombocyte, lymphocyte counts, D-dimer, alanine aminotransferase, aspartate aminotransferase, and procalcitonin) are recorded. Biochemical parameters and the necessity of oxygen support for the patients were evaluated on days 0, 3, and 7 of the first plasma treatment. Death risk covariates were analyzed. Described as moderate, severe, and critical, 199 patients were included in this study. The patients’ mean age of the patients was63.7±14.2 (min:24-max:93). Most patients were in the severe group (41.7%). The frequency of necessity of non-invasive mechanical ventilation/mechanical ventilation (NIMV/MV) support on day three and day seven was lower than on day 0 (p:0.004). C-reactive protein and procalcitonin levels were progressively decreased on day three and day 7 (p<0.001, p<0.001).Multivariate analysis showed that; ?65 years of age (HR:1.62 [1.06–2.49]),critical disease severity(HR:2.64 [1.10–6.30]), necessity of corticosteroid treatment (HR:2.22 [1.29–3.82]), leukocyte counts of ?4.23x103/UL (HR:2.10 [1.19–3.69]), lymphocyte levels of ?0.80 x103/UL (HR:1.74 [1.06–2.86]), AST levels of ? 50 U/L (HR:2.18[1.42–3.34]), and procalcitonin levels of ?0.5 ng/ml (HR:1.91 [1.26–2.91]) on day 3 were found independently associated with mortality. As a result, being older than 65 years old, having acute disease, receiving corticosteroids, having low lymphocyte-leucocyte counts, and having high ALT and procalcitonin levels are associated with mortality. Considering our findings, we think that more studies are needed in the patient groups.